(untitled) (Afrika und Übersee, 2022)
Labial-velar consonants, which are typologically rather rare in the languages of the world, have been used for both genealogical and areal classification purposes. The claim that their occurrence mainly signals areal contact (e.g. Güldemann 2008), has been criticized by scholars (cf. Cahill 2017, Childs 2017) who point out a possible genealogical development in multiple language families of Africa. In this paper, we analyse contemporary and historical data on Mbum varieties from the Adamawa plateau in Cameroon and closely related languages of the Kebi-Benue family to approach the question whether labial-velars are transmitted merely through contact in these languages or warrant a genealogical explanation. The bottom-up approach leads to an interpretation of the current distribution of labial-velars that has both elements in it: There are arguments for reconstructing labial-velars for the Proto-Kebi-Benue level, but certain specifics of their geographical distribution also hint at a contact explanation.